Language teaching research and language pedagogy - Ellis, Rod, 1944- (Wiley-Blackwell, 2012)
"This book examines current research centered on the second language classroom and the implications of this research for both the teaching and learning of foreign languages. It offers illuminating insights into the important relationship between research and teaching, and the inherent complexities of the teaching and learning of foreign languages in classroom settings."--Resumé vydavatele
Keywords: jazyková výuka; studium jazyků; jazyková akvizice; language teaching and learning; language learning; language acquisition; monografie; elektronické knihy; monographs; electronic books